Development of a direct competitive enzyme‐linked immunosorbent assay for quantitation of sodium saccharin residue in food. Issue 8 (26th July 2021) - Zhao, Yajie; Wang, Mian; Zhang, Man; Yang, Xiaolin; Li, ZhenFeng; Vasylieva, Natalia; Tan, Guiyu; Wang, Baomin; Hammock, Bruce D.
Abstract : Abstract: Sodium saccharin is a common artificial sweetener. However, due to its possible carcinogenic effects and causing metabolic disorders, many countries have strictly regulated its use in food. In the study, we prepared a specific monoclonal antibody (mAb 2H11) using the new hapten (6‐carboxylsaccharin) and developed a direct competitive enzyme‐linked immunosorbent assay (dcELISA) for the screening of sodium saccharin residue in food. The half‐maximum inhibition concentration (IC50 ) and working range (IC20 –IC80, the concentrations causing 20% and 80% inhibition by sodium saccharin) were 32.5 and 6.47 to 164 ng/mL, which was 6.5 times more sensitive than the previously reported immunoassay. The average recoveries of sodium saccharin in spiked food samples detected by dcELISA ranged from 82.1% to 117%. Among 70 food samples bought in the physical stores and online, sodium saccharin residues were only detected in four samples purchased online (one canned pineapple, two winter jujube, and one kimchi ). The content measured by dcELISA agreed well with those determined by ultra‐performance liquid chromatography‐tandem mass spectrometry (UPLC‐MS/MS). The developed dcELISA was proved to be a sensitive and accurate method for determining sodium saccharin in food. Practical Application: Quantitation of sodium saccharin residue in food is very necessary and important for consumers and regulatory agencies.